Integrating Religious Values in Schools: Strategies for Developing Student Religiosity - Suhartini, Andewi; Kamilah , Syarifah Aini; Ibrahim , Cindy Fatikasari; Maldani, Eva Syarifatul Ma'rifati Siti; Miftah , Khoirudin (Research Horizon, 2025)
This study aims to identify and describe strategies used by schools to develop students’ religiosity through religious culture, habituation, teacher modeling, and collaboration with families and communities. This research employed a qualitative approach with a library research design, analyzing accredited SINTA journal articles, academic books, and related studies. The results indicate that the development of students’ religiosity in schools is implemented through five main approaches. Religiosity is fostered through daily worship habituation, including congregational prayer, Qur’an recitation, voluntary fasting, and morning charity activities. Second, teachers and principals play a central role by serving as moral and spiritual role models for students. Schools create a religious environment by cultivating the 5S culture and displaying religious symbols. The implementation of innovative religious programs and digital-based learning supports students’ spiritual development in response to contemporary educational demands. The development of students’ religiosity is strengthened through collaboration among schools, families, and communities as part of the tri-center of education. The findings confirm that the development of students’ religiosity is not limited to formal Islamic education, but also requires an integrated and sustainable religious ecosystem that fosters faith, morality, and spiritual integrity among students.